PENGARUH LITERASI KEUANGAN DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN INVESTASI MAHASISWA EKONOMI MELALUI PERILAKU KEUANGAN SEBAGAI VARIABEL MEDIASI PADA MAHASISWA FAKULTAS EKONOMI UNISRI UNIVERSITAS SLAMET RIYADI SURAKARTA - Dafa Caesario Islama; Naili Amalia (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The results of the t-test showed that financial literacy has a significant effect on the investment decisions of students in the Faculty of Economics at Slamet Riyadi University Surakarta, while financial behavior does not mediate the influence of financial literacy and risk perception on investment decisions. The F-test result is 7.335 with a significance value (p-value) of 0.001 < 0.05. The determination coefficient test results showed an adjusted R2 value of 0.113 for this model, meaning that the independent variables Financial Literacy (X1), Risk Perception (X2), and Financial Behavior (Z) contribute 11.3% to the Investment Decision (Y). The remaining (100% - 11.3%) = 88.7% is contributed by other factors.The Sobel test results showed that the t-count for Z (Financial Behavior) mediating the influence of X1 (Financial Literacy) on Y (Investment Decision) is -1.326 < t-table (0.025; 98) = 1.98447, indicating that Z (Financial Behavior) does not mediate the effect of X1 (Financial Literacy) on Y (Investment Decision). Similarly, the t-count for Z (Financial Behavior) mediating the influence of X2 (Risk Perception) on Y (Investment Decision) is 0.39 < t-table (0.025; 98) = 1.98447, indicating that Z (Financial Behavior) does not mediate the effect of X2 (Risk Perception) on Y (Investment Decision).